(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Such processes in electric machines having sliding contacts as sparking and overheating can be the reason of the deep electroerosive wear. Searching effective ways to reduce sparking has an obvious practical significance since it extends the service life of the sliding contact in particular and service life of the electro-mechanic units in whole. This article contains information about physical processes in the electrical sliding contact. The method of spark suppression related to LC filters introduced to the electromagnetic brush circuits is considered, the device for spark reducing is suggested. The calculations of the impact of the device for spark reducing on sparking and thermal processes in the contact pairs are described.